Pengaruh Perilaku Masyarakat Terhadap Sanitasi Lingkungan di Kawasan Kumuh Kota Gorontalo - Fitriani, Maya (Universitas Muslim Indonesia, 2021)
This study aims 1) to determine the characteristics and patterns of community activities in sanitation management in the slum areas in Gorontalo City, 2) to find out the sanitary conditions in the slum areas in Gorontalo City, and 3) to find out the influence of communities’ behavior on environmental sanitation in the slum areas in Gorontalo City. This study was conducted in five slum areas in Gorontalo, those are Limba B Village, Biawao Village, Bugis Village, Botu Village, and Leato Selatan Village. The techniques and procedures used in this research are direct interviews and questionnaires with a Likert model of measurement scale. This study applies a quantitative method with Multiple Linear Regression analysis. This study discovers that 1) community characteristics and activity patterns are perceived by respondents in the good category. 2) The respondents perceive drainage, drinking water and clean water, wastewater, and solid waste in the good category. 3) The characteristics and patterns of community activities simultaneously have a positive and significant effect on environmental sanitation in slum areas, while partially only the activity patterns.